Traveling wave type solution in a model diffusive predator - prey type Holling II - Cortés-García, Christian (2021)
This paper demonstrates the existence of traveling waves as solutions for a predator - prey model with a Holling II predation function and a onedimensional diffusive term for predators. When performing a qualitative analysis on the model without diffusion, it follows that the model with diffusion presents periodic solutions. Similarly, by assuming a traveling wave-type solution to the diffusion model, it is shown that it has a heteroclinical orbit that connects two equilibrium points, attracted to one of them, and therefore presents wave fronts.